Evaluation of web-based distance education of medicine for undergraduates in Sri Lanka (Brief Report ) - Silva, D.; Randombage, P.; Gankanda, W.; Abeysekara, N.; Edirisinghe, V.; Chandratilake, M. (Sri Lanka college of Obstetricians & Gynaecologists, 2021)
INTRODUCTION Purpose: To evaluate distance education via the web facilitates teaching through problem-based learning and incorporating scientific evidence in the context of practical application to medical undergraduates. METHODS: Web-based distance teaching program based on the Zoom video conferencing software was developed and introduced into a selected group of medical students. Current knowledge about handling web-based resources, evaluation of learning activities, and self-evaluation of their involvement and participation of medical students were evaluated. RESULTS: The provision of lectures and relevant notes through the internet was emphasized during this study. A satisfactory response was observed regarding obtaining factual knowledge. This method was considered relatively ineffective with relevance to the application of knowledge, development of clinical skills, and improvement of professional attitudes. Students believed that it helped to improve the ability of critical thinking, refine reasoning skills, and enhance the capacity of mediating subject matter. Students had a general idea regarding using this method as a supplementary education strategy. The majority of the participants demonstrated considerable satisfaction towards this method, and most of them were prepared to recommend this method for another person. The students had disclosed that lectures showed significantly higher skills while teaching through this method, especially they believed that this distant learning method provided an additional benefit for face to face clinical teaching procedures. CONCLUSION: When generally considered, a satisfactory response was received regarding the learning outcomes of using this method, and the quality of participation of students was extremely positive. KEYWORDS: Distance education, Web-based learning, Undergraduates teaching
Not indexed in MEDLINE
Keywords: distance education; undergraduates